Role of Education in the Empowerment of Women in India - Harun Al Rasid Mondal (PT Publikasiku Academic Solution, 2023)
Education is not only the main pillar of nation-building, but through education, a nation moves towards progress. In a country, with different races of people, both men and women became uplifted towards development when illuminated by education. By the united force of men and women, especially women, a country leads its way to the path of success. Women’s empowerment is a necessity for this success. Again, education is the most powerful instrument of empowerment as it generates consciousness that leads to empowerment. Hence, to pave the way for women’s emancipation and empowerment, education plays a pivotal and inevitable role. According to Pandit Jawaharlal Nehru –